MAGNITUDE AND FACTORS ASSOCIATED WITH LOW BIRTH WEIGHT AMONG WOMEN DELIVERED IN PUBLIC HOSPITALS OF BENCH MAJI, KEFFA AND SHEKA ZONES SOUTH WEST OF ETHIOPIA, 2018 - Abera Gudeta, Tesfaye; Mekonnen Regassa, Tilahun; Chewaka Gamtesa, Lalisa; Lolaso Lenjebo, Tsegaye; W/kidan Mengistu, Fekede (Ethiopian Journal of Reproductive Health, 2019)
BACKGROUND: The burden of low birth weight has decreased dramatically worldwide in the past 40 years. Despite this, there is still a large gap between the developing and developed countries. Ethiopia is one of the developing countries with limited data on the prevalence and main risk factors of low birth weight. Therefore; providing information on this problem is very important for planning maternal and child health care services. OBJECTIVE: To assess the magnitude and factors associated with low birth weight among women delivered at Mizan-Tepi university teaching hospital, Tepi general hospital, Wacha hospital and Gebretsadik Shawo hospitals Southwest, Ethiopia, 2018. METHODS: A cross-sectional study was conducted at selected hospitals on all women who gave birth during study period. Data was entered to Epidata version 3.1 and exported to SPSS version 20 for analysis. Logistic regression analysis was carried out to identify associated factors at confidence interval of 95% and significance level of P-value<0.05. RESULT: The magnitude of low birth weight was 7.5%. Educational status of the mother [AOR 3.6, 95% CI (1.46-8.92)], iron intake during pregnancy [AOR 2.88, 95% CI (1.37-6.05)], Current pregnancy complication [AOR 5.98, 95% CI (3.37-10.62)], induced labor [AOR 2.37, 95% CI (1.08-5.12)] and gestational age [AOR 37.61, 95% CI (20.61-68.56)] were significantly associated factors with low birth weight. CONCLUSION: The magnitude of low birth weight was found to be high in the study area. Educational status of the mother, iron intake during pregnancy, pregnancy complication, induced labor and gestational age were identified predictors of low birth weight. KEY TERMS: Low Birth Weight, Pregnancy, Delivery, Women.